COVID-19 and the school-based mass preparticipation physical evaluation: The anvil that broke the camel`s back? - Cunningham, A. (Annals of Family Medicine, 2020)
The preparticipation physical evaluation is required in the vast majority of states for participation in high school athletics. These examinations are commonly performed at school- based mass events. Given the current climate surrounding the COVID-19 pandemic and recommendations for social distancing, primary care and sports medicine providers should use this opportunity to encourage athletes to have their preparticipation physical evaluations performed by their primary care provider in their medical home in accordance with recommended best practices both now and in the future. The school-based mass preparticipation physical evaluation should not return in the post-COVID world